Klasifikasi Tanah Menurut Pengetahuan Masyarakat Lokal pada Lithosekuen Lahan Pertanian di Desa Latawe, Muna Barat - Septyawati, Eka Nindya; Hemon, M. Tufaila; Alam, Syamsu; Zulfikar, Zulfikar; Rustam, La Ode; Yusuf, Dewi Nurhayati (Jurnal Agroteknologi (Agronu), 2025)
Soil classification is needed because each type of soil has specific properties and characteristics, potential and constraints for certain uses. This study aims to classify soil according to local community knowledge on agricultural land lithosequences and their equivalents based on Soil Taxonomy in Latawe Village, West Muna Regency. The research method used is a free survey method that refers to the Geological Map Unit (SPG) with the type of soil profile observation. Soil classification according to local knowledge is carried out using a qualitative method with a social approach by interviewing the local community of Latawe Village and then matching the soil classification based on USDA Soil Taxonomy. The results of soil classification on agricultural land lithosequences according to local community knowledge are in SPG 1A (alluvium parent material) classified as wite kakuni (yellow soil), SPG 2A (limestone parent material) classified as wite kaghito (black soil), SPG 1B (alluvium parent material) classified as wite bhone (sandy soil), and SPG 2B (limestone parent material) classified as wite awu (calcareous soil). The results of soil classification according to local community knowledge are matched with Soil Taxonomy, namely profile I is included in the Inceptisols order, profile II is included in the Alfisols order, profile III is included in the Ultisols order, and profile IV is included in the Vertisols order. Lithosequences contribute to different soil properties and characteristics, both classified according to local farmer knowledge and the Soil Taxonomy system